Botany as a New Field of Knowledge in the Thirteenth Century: On the Genesis of the Specialized Sciences - Mustafa Yavuz; Pilar Herraíz Oliva (Teorie vědy, 2020)
The reception of the translations of Aristotelian and pseudo-Aristotelian works at the University of Paris in the thirteenth century promoted a new understanding of the sciences as specialized fields of knowledge. The huge amount of translations required a new organization of knowledge, which included novel subjects and categories. Among these there is a very special case, namely the pseudo-Aristotelian De plantis, translated from Arabic into Latin and then back into Greek to be re-translated into Latin again. De plantis was included in the new curriculum in Ripoll 109 (1230–1240 BCE), and constituted the main source for botanical studies until the sixteenth century. Throughout this paper we will explore the reception and impact of De plantis in both the Arabic and the Latin traditions. We aim to show its foundational role in the development of botany as a theoretical discipline within the natural sciences.